Fenofibrate-associated rhabdomyolysis complicated by dialysis-requiring acute kidney injury presenting with atypical clinical manifestations - Yumei Fang; Yan Jiang (Medicine, 2026)
Rationale: Rhabdomyolysis (RM) may cause acute kidney injury (AKI), but the classic triad of myalgia, muscle weakness, and dark-colored urine is often absent. Fenofibrate-associated RM is rare and may be overlooked in older patients with chronic kidney disease (CKD), reduced renal reserve, or polypharmacy. Patient concerns: A 70-year-old man with CKD was admitted with nausea, poor appetite, and a marked increase in serum creatinine for 1 week. Two months earlier, atorvastatin had been discontinued, and micronized fenofibrate had been started for hypertriglyceridemia. He had no obvious myalgia, muscle weakness, or dark-colored urine. Diagnoses: Serum creatinine rapidly increased from approximately 130 μmol/L to 1132–1202 μmol/L. Peak creatine kinase (CK) was 28,831 U/L, and serum myoglobin was 915 ng/mL, accompanied by metabolic acidosis, hypocalcemia, and hyperphosphatemia. Based on the temporal association with fenofibrate exposure, marked muscle enzyme elevation, improvement after drug withdrawal, and absence of common alternative triggers, the patient was diagnosed with probable fenofibrate-associated rhabdomyolysis complicated by KDIGO stage 3 AKI superimposed on underlying CKD. Interventions: Fenofibrate was discontinued immediately. The patient received fluid therapy, correction of metabolic acidosis, electrolyte monitoring and management, and supportive kidney care. Because he initially refused dialysis, intermittent hemodialysis (IHD) was initiated on hospital day 10 for persistent uremic symptoms, severe AKI, and metabolic derangements. Net ultrafiltration was set at 0 mL to avoid further volume depletion. Outcomes: After IHD and supportive treatment, gastrointestinal symptoms improved, urine output increased, and CK and renal function gradually improved. Dialysis frequency was reduced after discharge, and IHD was discontinued 5 weeks later. At 8 months after discharge, serum creatinine had decreased to 157 μmol/L, and CK and myoglobin remained normal. Lessons: In older patients with CKD, eGFR should be calculated before fenofibrate is prescribed, and dosing should follow the product label. Unexplained renal deterioration or nonspecific symptoms after fenofibrate exposure should prompt measurement of CK and myoglobin. Immediate drug withdrawal and supportive treatment are essential, whereas IHD should be reserved for standard AKI indications.